Body Pose Estimation Integrated With Notational Analysis: A New Approach to Analyze Penalty Kicks Strategy in Elite Football - Pinheiro, Guilherme de Sousa; Jin, Xing; Costa, Varley Teoldo Da; Lames, Martin (Frontiers in Sports and Active Living, 2022)
Body orientation of football players has proven to be an informative resource related to successful penalty kicks. OpenPose is one of the most popular open-source pose estimation technologies. This study aims (i) to verify whether OpenPose can detect relevant body orientation angles from video data of penalty kicks in elite football; and (ii) to investigate the relation between these body angles and observable behaviors analyzed via an observation system for penalty kick analysis in football (OSPAF) with the penalty taker and goalkeeper strategy. A total of 34 penalty videos, with standardized viewing angle, from the main European leagues (2017-2020) were analyzed. Relevant body orientation variables were selected for penalty kicks analysis and were extracted from video data through the OpenPose technique. The OSPAF, previously validated by experts, was used. The mean confidence score of OpenPose measures was 0.80 ± 0.14. The mean kappa value for repeated measurements of the OpenPose was 0.96 ± 0.04. Logistic regressions were performed to investigate the relationship between OpenPose investigated variables (penalty taker: shoulder, hips, and non-kicking foot orientation; goalkeeper: right and left foot, anticipation), observable behaviors (OSPAF variables) and the strategy (penalty taker: goalkeeper dependent or independent; goalkeeper: shooter dependent or independent) in penalty kicks. The selected body orientation angle (goalkeeper anticipation) measured through OpenPose, correlated significantly with the goalkeeper strategy. The prediction model of the goalkeeper's strategy had its accuracy increased to 97% when the variable goalkeeper anticipation was included (χ2 (35) = 49.648, p < 0.001). Lower degrees of goalkeeper anticipation, the goalkeeper tactical action (awaiting) and run up speed (slow) were associated with a kicker dependent strategy. Regarding the penalty taker, the selected body angles measured through OpenPose did not associate significantly with the shooter strategy. Body orientation analysis using Openpose has shown sufficient reliability and provides practical applications for analyzing the strategies adopted by goalkeepers in penalty kicks in elite football.